ANALISIS SISTEM PENGADAAN SUMBER DAYA MANUSIA PADA PT L : MENYELARASKAN STANDAR GLOBAL DENGAN KONTEKS TENAGA KERJA LOKAL - Amira Fachrisa Gumay; Christian Wiradendi Wolor (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the human resource procurement system at PT L, including the implementation of human resource procurement, the effectiveness of recruitment and employee placement processes, and the challenges faced by the company along with the solutions applied. This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation. The informants consisted of one Human Resources Development (HRD) Manager and one employee of PT L selected through purposive sampling. The findings show that the human resource procurement system at PT L has been implemented systematically through workforce planning, recruitment, selection, and employee placement. The recruitment and placement processes were considered effective because they were based on job requirements and candidate competencies. However, the company still faces several challenges, including the limited availability of candidates who meet foreign language proficiency standards, low candidate responsiveness, and delays in feedback from users. To overcome these challenges, the company collaborates with universities, conducts regular follow-ups with users, and utilizes headhunter services for specific positions. Overall, the human resource procurement system at PT L has been implemented effectively and supports organizational needs.